VD_FINDINFO Décision / 2014 / 943 vom 18. August 2014 - VD Tribunal cantonal (2014)
HOMICIDE PAR NÉGLIGENCE, SUICIDE, DILIGENCE, NÉGLIGENCE, ÉTABLISSEMENT HOSPITALIER | 117 CP, 12 al. 3 CP, 319 CPP (CH)